Innovation and beyond - Nantel, JH (Mine Fill 2014: Eleventh International Symposium on Mining with Backfill, 2014)
Does a low level of innovation condemn the mining industry to mediocrity or failure? What lessons can the mining industry draw from other industrial sectors? In the high tech world, failure to innovate is the kiss of death. How did Blackberry manage to blow its runaway lead and become a minor player in the smartphone market it invented? Can the same destiny be lurking for mining corporations that fail to innovate? Mine backfill represents a core area where innovation could benefit the entire mining operation. The filling process controls how fast and how well a mine operates. The mining industry is beginning to show a renewed interest in mine research. Is this more talk than action? Some will point out that the mining industry never recovered from the research and development (R&D) slowdown that followed the productive period of the 1980s and 1990s. The author will explore the parallels between industries and outline a blueprint for what the mining companies need to do to stay competitive. The model proposed will require the leaders of the large mining companies to take charge of innovation. The model is simple: big companies, big ideas and big contributions. The mining industry must continue to innovate to remain viable.